Progressive Epidural Hematoma in Patients with Head Trauma: Incidence, Outcome, and Risk Factors - Hao Chen; Yan Guo; Shi-Wen Chen; Gan Wang; He-Li Cao; Jiong Chen; Yi Gu; Heng-Li Tian (Emergency Medicine International)
Progressive epidural hematoma (PEDH) after head injury is often observed on serial computerized tomography (CT) scans. Recent advances in imaging modalities and treatment might affect its incidence and outcome. In this study, PEDH was observed in 9.2% of 412 head trauma patients in whom two CT scans were obtained within 24 hours of injury, and in a majority of cases, it developed within 3 days after injury. In multivariate logistic regression, patient gender, age, Glasgow Coma Scale (GCS) score at admission, and skull fracture were not associated with PEDH, whereas hypotension (odds ratio (OR) 0.38, 95% confidence interval (CI) 0.17–0.84), time interval of the first CT scanning (OR 0.42, 95% CI 0.19–0.83), coagulopathy (OR 0.36, 95% CI 0.15–0.85), or decompressive craniectomy (DC) (OR 0.46, 95% CI 0.21–0.97) was independently associated with an increased risk of PEDH. The 3-month postinjury outcome was similar in patients with PEDH and patients without PEDH (χ2=0.07, P=0.86). In conclusion, epidural hematoma has a greater tendency to progress early after injury, often in dramatic and rapid fashion. Recognition of this important treatable cause of secondary brain injury and the associated risk factors may help identify the group at risk and tailor management of patients with TBI.